Tom Clancy chain of command - Cameron, Marc (Clancy, Tom, 1947-2013. Jack Ryan novel., 2021)
To implement his most ambitious plan of all, a ruthless billionaire must get President Jack Ryan out of the way and assembles the most ruthless mercenaries alive to kidnap the First Lady.